2013
DOI: 10.1371/journal.pgen.1003440
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Differential Selection and the Evolution of X Inactivation Strategies

Abstract: X inactivation—the transcriptional silencing of one X chromosome copy per female somatic cell—is universal among therian mammals, yet the choice of which X to silence exhibits considerable variation among species. X inactivation strategies can range from strict paternally inherited X inactivation (PXI), which renders females haploid for all maternally inherited alleles, to unbiased random X inactivation (RXI), which equalizes expression of maternally and paternally inherited alleles in each female tissue. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…However, several studies have reported variants that lead to severe skeletal abnormalities among women, resembling the osteoporotic phenotype of men [108,115,[128][129][130]. This huge variation in heterozygous women is suggested to be caused by X-inactivation of the mutant allele or PLS3 escaping X-inactivation which is why women are less severely affected [15,126,129,131,132]. Even though bone morphometry was very heterogeneous [16,126,[133][134][135][136], most male patients showed peripheral fractures, low BMD, VCFs, especially in the thoracic spine, and low bone turnover rate, while only a few developed extraskeletal OI traits [108, 126-128, 131, 137-140], developmental delay [15,127] or neuromuscular abnormalities, like waddling gait [108,126,131,141].…”
Section: Osteoporosismentioning
confidence: 99%
“…However, several studies have reported variants that lead to severe skeletal abnormalities among women, resembling the osteoporotic phenotype of men [108,115,[128][129][130]. This huge variation in heterozygous women is suggested to be caused by X-inactivation of the mutant allele or PLS3 escaping X-inactivation which is why women are less severely affected [15,126,129,131,132]. Even though bone morphometry was very heterogeneous [16,126,[133][134][135][136], most male patients showed peripheral fractures, low BMD, VCFs, especially in the thoracic spine, and low bone turnover rate, while only a few developed extraskeletal OI traits [108, 126-128, 131, 137-140], developmental delay [15,127] or neuromuscular abnormalities, like waddling gait [108,126,131,141].…”
Section: Osteoporosismentioning
confidence: 99%
“…A recent theoretical population genetic analysis shows that the interaction between allelic dominance and sex-differential selection can generate a broad and continuous range of XCI scenarios, including unequal rates of inactivation between maternal and paternal X chromosomes. rXCI is favored over strict pXCI when alleles deleterious to females are sufficiently recessive (Connallon and Clark, 2013).…”
Section: Dosage Compensation: the Heritage Of Lyon And Ohnomentioning
confidence: 99%
“…There are currently no experimental data that shed light on the expected h value for X-linked deleterious variants in mammals (Connallon and Clark 2013), although mutation-accumulation experiments for the X chromosome in Drosophila melanogaster are suggestive of dominance coefficient of 0.3 (Mallet et al 2011). Mank et al (2010) suggested h ¼ 0.5 may be a reasonable value to mimic the effects of X inactivation in therian mammals.…”
Section: Uncertainties In Estimating Hmentioning
confidence: 99%